Investigation of the synthesis, gelation potential, and drug-loading capacities of two novel amides - Bariş Cebe, Deniz; Kötekoğlu, Elif (Frontiers in Chemistry, 2024)
This study consists of four steps. At the first phase, two different biocompatible organogelators were synthesized starting from L-isoleucine amino acid to obtain amide compounds. At the second, gelation potential of synthesized organogelators with fatty acid esters, and organic solvents were investigated. The employed fatty asid esters were chosen as gelation liquids due to being biocompitable and also having properties that increase penetration while the drug is given via skin. After the minimum gel concentrations (MGC) of organogelators were determined, the melting point of gels Tg was found, and then ΔHg gelation enthalpy values were found by means of van't Hoff equation. In addition to gelation abilities and capacities of organogelators synthesized in this way, their thermal stabilities were also determined. At the third phase of the study, the network which occurred during the formation of gels was screened by means of SEM device and their characterizations were made. At the fourth phase of the study, the gels were loaded with ibuprofen and naproxen known for their non-steroidal anti-inflammatory and analgesic effects, thus their drug loading capacities were determined.